ANALISIS PENDAPATAN DAN TINGKAT KESEJAHTERAAN RUMAH TANGGA PETERNAK SAPI PERAH ANGGOTA KOPERASI PETERNAKAN BANDUNG SELATAN (KPBS) PANGALENGAN - Quen Tia Mona; Dyah Aring Hepiana Lestari; Suriaty Situmorang (Lampung University, 2014)
The objectives of this research were to find out: (1) dairy farming business income of animal husbandry farming cooperation’s member in South Bandung (KPBS); (2) contributions of economic benefits of cooperation (MEK) to the family income of KPBS’s members; (3) welfare level of KPBS’members. This research was conducted in KPBS working area of cooperation activity center in Pangalengan sub district; the TPK Mekar Mulya and TPK Pangalengan. The locations were selected purposively. Data were collected from February to April 2013. Samples of 61 respondent were taken using proportional random sampling. This research used descriptive qualitative analysis method. The results showed that (1) the farmer’s income of KPBS’s member on total cost was Rp8,87,849.56 annually per dairy farming business or Rp2,681,422.59 annually per unit of dairy cow; (2) the economic benefits of cooperation (MEK)amount to perceive directly in non-cash was Rp1,039,832.13 annually. The MEK amount to perceive indirectly in cash was Rp1,458,622.96 annually, and it contributed 5.35% family income of KPBS’s member; (3) 14.75% of KPBS’s member (9 families) were poor and considered as not welfare families.Key words : breeder, dairy cattle, income, MEK, welfare